The Impact of Organizational Culture, Dual Roles, and Work Environment on Hotel Performance with Work Effectiveness as a Mediating Variable: (Case Study of MaxOne Hotel Jakarta Post-Acquisition) - Juwita, Rekke; Nurbaeti, Nurbaeti; Asmaniati, Fetty (Ann Publisher, 2025)
Background. The corporate culture, work environment, and dual functions of each corporation vary. For organizations that are acquired by another, employees must experience a meaningful impact. Organizational culture, work environment, and dual roles are vital, as these factors significantly contribute to the advancement of the organization, especially in the hotel industry. These three criteria can ascertain the efficacy of employee performance and the overall operational success of the hotel. Aims. This research investigates these five variables. This study aimed to examine the impact of these variables. The study was carried out in five hotels affiliated with the Artotel Group: Nite and Day Mangga Besar, All Nite and Day Kebon Jeruk, Zia Sanno Menteng, MaxOne Kramat, and MaxOne Sabang. Methods. The method used was SEM PLS, with the samples studied being hotel employees. The sampling technique used in this study is Non-Probability Sampling. Result. The results of this study indicate that the variables of organizational culture, dual positions, and work environment influence hotel performance through work effectiveness, serving as an intervening variable.